Local Insights, Global Ethics for Business - Koehn, Daryl (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This book evaluates strategies for managing ethical conflict. Macro-approaches that attribute select values to entire peoples and claim supremacy for these values are suspect. A micro-approach, focusing on the ethics of individual thinkers, is better. The study uses the ethics of Confucius and Tetsuro Watsuji to derive a process-based universal ethic that respects local differences yet is not relativistic.